ANALISIS KESESUAIAN AKUNTANSI RAHN EMAS DALAM PERSPEKTIF PSAK PADA HADITS IMAM BUKHARI - Agustin, Yuliana; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out the accounting treatment sharia gold pawn product at Sharia Islamic pawnshop Surabaya with gold pawn practice case study on Islamic pawnshop Blauran branch Surabaya which has been set out in the SFAS and measured its compatibility with the hadith of Imam Al-Bukhari. The legal basis of sharia pawn in Indonesia is using the hadith of Imam Al-Bukhari that has been used as a reference, i.e., the story of armor, the story of mounts or vehicles and the story of anshar men. The gold pawn products in the accounting treatment is regulated in the SFAS 59 (qardh), the SFAS 107 (Ijara) and the PAPSI of 2013. The result of the research shows that the contract which has been used in Sharia pawnshop has been carried out by using rahn, qardh and Ijara contract. In the aspect of measurement and recognition it has been performed in accordance with the SFAS 59 about (qardh contract), the SFAS 107 about (Ijara contract) and PAPSI of 2013. However, there are things that are not in accordance with the hadith of Imam Al-Bukhari and Muslim that is the loan on qardh financing, the determination of the administrative costs is based on the amount of the loan, the classification of the percentage ijarah discount rate and the combination of qardh and ijara contract. As it is in accordance with the hadith of Imam Al-Bukhari Muslim that the system costs Ijara, full repayment, and auctions.Keywords: SFAS 59 (qardh), SFAS 107 (ijara), PAPSI of 2013, the Hadith of Imam Bukhari.